Nilai-Nilai Pendidikan Dalam Budaya Tarung Presean Di Lombok Barat (Perspektif Agama Hindu) - I Made Ardika Yasa (Jayapangus Press, 2020)
Tarung Presean Culture in Batu Kumbung Village, Lingsar Subdistrict, West Lombok Regency, there are several components that can be examined in the presentation of results including: (a) Tarung Presean Culture is carried out by the Hindu Balinese who have long lived on the island of Lombok along with the Muslim Sasak tribe with a variety of social statuses but one goal is to ask for the gift of rain in order to obtain fertility and commemorate the services of the ancestors and as a form of thanks to the spirits of their ancestors who have fought to achieve independence and unite the archipelago. The culture of Tarung Presean in Batu Kumbung Village, Lingsar District, goes through several stages, namely; (1) preparations include making arenas, providing tools for Tarung Presean, and appointing referees (Pekembar), (2) Introduction marked by the beating of Sasak gamelan instruments accompanied by Sasak version of Pancasila songs, (3) the peak of the Ceremony designating an audience to be Pepadu and Tarung Presean begins after Pepadu is determined and ready to fight, (4) closing ceremony, a pair of Pepadu who have competed with each other / hugged each other and the committee gives gifts to fighters and gives closing words to the audience and fighters / Pepadu about the meaning contained in Tarung Presean. (b) In studying the values ​​of Hindu religious education contained in the culture of Tarung Presean in the Batu Kumbung village of Lingsar sub-district, West Lombok Regency, using the Hindu Religious Concept which refers to the holy books, namely: Vedic Scriptures, Bhagavad Gita, Manawa Dharmasastra, and Sarascamuccaya. (c) In Tarung Presean in Lingsar Temple, Lingsar Subdistrict, West Lombok Regency, there are aesthetic aspects, logic aspects, and ethical aspects as well as very deep meaning, including; (1) Tarung Presean as Actualization of Self-Control, (2) Tarung Presean as a form of Sportmanship and Patriotism, and (3) Tarung Presean Application from Tri Hita Karana.